The Representation of Ideal Women in German Fairy Tales Written by The Brothers Grimm - Tira Murniati Yusuf (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
The patriarchal culture, which can be tracked down in most societies around the world, constructs the concept of ideal women. In this system, a woman is considered an ideal woman only if she represents particular traits. This study aimed to examine the representation of ideal women in the structure of selected German fairy tales by The Brothers Grimm. The method used in this study was descriptive qualitative. The five selected German fairy tales were Cinderella, Snow White, The Six Swans, The Twelve Brothers, and The Three Little Menin the Woods. To analyze those stories, the theory used in this study was Propp’s framework in describing tales, particularly Narrative Structure and Dramatic Personae.The results revealed that the structure of Brother Grimm’s fairy tales showed the traits of ideal women that are portrayed by the heroines of all the selected fairy tales as a consequence of the concept of ideal women constructed in the society. On the other side, the representation of non-ideal women is also demonstrated by the villains in the fairy tales.